Selection Criteria Optimisation for Ankole Beef Cattle: Productivity Enhancement Strategies in Kwimba, Tanzania - G.L. Chasama; H.F. Massawe; N. Felix; A.C. Mwang’imba; C.J. Niyoifasha; A.N. Francis.; P. Rukiko; W.V. Kikoti; A.R. Kamugisha (New Advances in Business, Management and Economics Vol. 6, 2025)
Beef is among the animal proteins most consumed by the rapidly growing population of urban dwellers in sub-Saharan Africa. Beef productivity improvement is crucial because ruminant production currently faces challenges of depleting production resources and growing concerns about raising methane emissions, but at the same time required to feed the growing human population. Ankole cattle, which belong to the Sanga group, have been among the native breeds considered for crossbreeding. Economic and animal performance data were collected from the Ankole herd of Tanzania Livestock Research Institute (TALIRI)-Lake Zone, and progressive farmers were used to analyse economic values of beef traits. Sequential bio-economic modelling methodology involving the formulation of a profit function was used to estimate economic values of traits influencing investment and revenues of beef production. Primary data were collected on feeding, veterinary drugs, and labour costs were estimated based on the previous production cycle from October 2023 to September 2024. Data analysis was done using the sequential bioeconomic modelling procedure. The procedure went through specification of the production and marketing system, identification of sources of income and costs, determination of biological traits linked to the profitability of beef production and derivation of economic values of the traits. The fecundity trait studied was calving interval, which generated an economic value of 833.15. Developmental traits analysed were age at maturity and age at first calving, which generated economic values of 83.86 and 19, respectively. Weaning weight generated a very high positive economic value of 1496.18, contrary to other studied growth traits (body weight and post-weaning daily gain, which generated economic values of -6.09 and -53.69, respectively). Longevity displayed a negative economic value of the lowest magnitude (-4.03). Therefore, under the prevailing conditions, selection for growth traits, which is normally prioritised in breeding for beef, showed low potential for impacting profitability improvement. Lowering the herd mean for calving interval is among the key productivity enhancement strategies for the farm. It was concluded that, in order to realise the benefits of selection, there is a need to parallel the genetic improvement initiative with strategies for lowering production costs, particularly feed costs. To realise the potential of improving cattle genetics in the Tanzania Lake zone, there is a need to parallel genetic improvement initiatives with initiatives targeting the development of alternative feeding systems for cattle.